Effects of combined application of selected food waste as bio-fertilizer on the growth of Capsicum annuum L. - Musa, Nor Lailatul Wahidah; Razali, Muhammad Halim; Shaikh Nasir, Nur Thabitah; Md Isa, Nurun Nadhirah; Nawi, Liliwirianis; Mohd Jan, Sarah Laila (GADING Journal of Science and Technology, 2023)
Excessive use of synthetic fertilizer will cause a lot of damage to the environment. Household waste products have been proposed to replace synthetic fertilizers and be recycled into safe fertilizers for sustainable agriculture. Therefore, this study was conducted to determine the effects of a combined application of selected food waste from onion waste (OW), coffee grounds (CG), and eggshell (ES) at various ratios on the morphological growth of Capsicum annuum L (chili). Seedlings of C. annuum were treated in three different ratios of treatment (Treatment A (3OW:2CG:1ES), Treatment B (2OW:3CG:1ES), and Treatment C (1OW:2CG:3ES) for eight weeks. The seedlings were also placed under NPK fertilizer (positive control) and without fertilizer (negative control) as a comparison. Measurements of plant growth (height, stem diameter, and number of leaves) were made at frequent intervals. Treatment A ratios enhanced the growth characteristics of C. annuum higher than the positive control (NPK fertilizer), with a significant increase observed particularly in the height and growth rate of the number of leaves (p ≤ 0.05). Treatments B and C were also effective in increasing the growth of C. annuum plants, but not as effective as treatment A. However, seedlings under treatment A showed lower growth in diameter compared to the positive control (NPK fertilizer). These results unveiled the potential of food waste as a promising biofertilizer, but further research is needed to comprehensively increase all the growth parameters with the use of enhancers.